The Relationship Between Carbohydrate and Saturated Fat Intake with Acne Vulgaris in Grade 3 Female Students at Department of Nutrition Poltekkes Kemenkes Surabaya - Shofi Khoirunnisa; Ani Intiyati; Nur Hatijah (Journal of Nutrition Explorations, 2023)
Acne vulgaris is the top 3 most common skin diseases. Nutritional intake of carbohydrates with a high glycemic index and saturated fat has a significant effect on the pathogenesis of acne vulgaris. Based on an initial study in January 2021, the results showed that 63.6% of female students were experiencing acne. The purpose of this study was to determine the relationship between carbohydrate and saturated fat intake with the incidence of acne vulgaris in grade 3 female students at the Department of Nutrition Poltekkes Kemenkes Surabaya. This research method uses analytic observational with a cross sectional approach. The sample consisted of 70 female students who were taken using a simple random sampling system. Data on carbohydrate and saturated fat intake were obtained by filling out the SQ-FFQ form. Data analysis used Spearman's Rank test. The results showed that there was a significant relationship between carbohydrate and saturated fat intake and the incidence of acne vulgaris with a p-value of 0.000; 0.000 (p=0.05) and the number of the correlation coefficient is 0.707 respectively; 0.791. It is recommended that the intake of carbohydrates that contain a high glycemic index and saturated fat need to be limited.